WHAT DISTINGUISHES CONNOISSEURS FROM SPENDERS? A CASE STUDY OF WINE IN CROATIA - Ilak Peršurić, Anita Silvana; Mann, Stefan (Economics of Agriculture, 2019)
This paper had a goal to explore the knowledge and spending power, which frequent criteria are for target groups, although they are rarely distinguished in a systematic way. This paper develops motivation for a thorough distinction and reveals differences among connoisseurs and spenders within the Croatian wine market. A theoretical model of the two target groups in a framework around the BCG matrix was developed. For the empirical verification, standardized face-to-face interviews were conducted with 307 Croatian wine consumers. For the sake of knowledge, both self-reported and observed measures were used. Our findings confirm that Connoisseurs emphasize particularly functional characteristics of wine that constitute self-related items such as self-fulfillment and social values, while spenders rather emphasize the gastronomy experience of wine. The difference between connoisseurs and spenders can be translated into marketing strategies that emphasize different product attributes and characteristics of wine at different stages of the product life cycle.